Labour market fluctuations and the housing net worth channel in the EU - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2021)
The credit-driven housing net worth channel has been identified as a determinant of the sharp drop in US employment between 2007 and 2009. We examine the impact of this channel on the labour market in Europe using panel data for 20 countries covering the period 1996 to 2017. This period saw substantial changes in both credit provision and labour market performance in the EU. While some of our results are similar to those found in analysis of the US labour market, there are also important differences. For the full panel, we find changes in housing net worth having a significant effect on total employment and its non-traded and traded sector components, with a larger effect in the non-traded sector. Further estimations show that these significant effects on employment pertain to the post-2007 era when credit conditions were considerably more restrictive. In contrast to the US evidence, we find significant wage responses to housing net worth shocks arising in the EU.
Keywords: E24; E32; E51; 330; Housing Net Wealth; Employment; Wages